ANALISIS SWOT DAN STRATEGI PENGEMBANGAN BERKELANJUTAN UNTUK UMKM DI DESA WISATA SAUNG CIBURIAL - Dwi Santy, Raeni; Abdul Gani, Salman; Riansyah, Alan; Bagja Sudrajat, Lutfi (ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
Saung Ciburial Tourism Village holds significant potential for the development of Micro, Small, and Medium Enterprises (MSMEs), yet it faces various challenges that impact its sustainability and competitiveness. This initiative aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) faced by MSMEs in Saung Ciburial Tourism Village and to formulate effective sustainable development strategies. The methods used in this initiative include surveys, in-depth interviews, and secondary data analysis to identify the internal and external factors affecting MSMEs. The SWOT analysis results indicate that MSMEs in Saung Ciburial Tourism Village possess strengths such as unique local products and strong community support, but also face weaknesses such as limited access to technology and capital. Opportunities that can be leveraged include the increasing interest of tourists in local products and government support for tourism development. Keywords: Sustainable development strategies; MSMEs; Ciburial Tourism Village; technology; marketing